DINAMIKA PDRB KABUPATEN/KOTA DI BALI: PERAN IPM, TPT, PAD, DAN PERIODE PANDEMI COVID-19 - Made Sinthya Aryasthini Mahaendrayasa; Ida Ayu Gde Dyastari Saskara; I Made Putra Yasa Putra; I Wayan Priyana Agus Sudharma (Yayasan Nusantara Hasana Berdikari, 2026)
This study examines the determinants of regency/city gross regional domestic product at current prices (GRDP-CP) in Bali during 2017-2025, focusing on human development, unemployment, local fiscal capacity, the COVID-19 shock, and the SARBAGIA area dummy. A balanced panel of 81 observations covering nine regions and nine years is estimated using a cross-section random-effects Panel EGLS model with White-period robust standard errors. GRDP-CP is reported in billion rupiah, while local own-source revenue (PAD) is also presented in billion rupiah. The results show that the Human Development Index is positively associated with nominal GRDP, the open unemployment rate is negatively associated with nominal GRDP, and PAD has a positive elasticity. The COVID-19 and SARBAGIA dummies are statistically insignificant. The findings underline the roles of human capital, labor-market conditions, and local fiscal capacity in explaining differences in the nominal scale of regional economies in Bali.